Comparison of Bone Marrow Biopsy and Flow Cytometry in Demonstrating Bone Marrow Metastasis of Neuroblastoma - Esra Arslantaş; Ali Ayçiçek; Selvinaz Özkara; Ayşe Özkan Karagenç; Sibel Akpınar Tekgündüz; Duygu Yıldırgan; Tuba Nur Tahtakesen Güçer; Ayşe Gonca Kaçar; Özgü Hançerli; Saide Ertürk; Ezgi Paslı Uysalol; Cengiz Bayram (Diagnostics)
Objective: This study aimed to compare bone marrow aspirate (BMA) multicolor flow cytometry (MFC) analysis and bone marrow biopsy (BMB) in detecting bone marrow (BM) involvement in children with neuroblastoma (NB) at diagnosis and during follow-up. Materials and Methods: A total of 132 BM samples from 39 patients (M/F ratio: 19/20; median age: 38 months) with neuroblastoma were simultaneously obtained for evaluation. The samples were investigated for BM involvement using BMB and MFC. Results: A comparison between MFC (n: 60) and BMB (n: 60) was possible for 120 samples. When BMB was considered as the reference standard, MFC had diagnostic sensitivity, specificity, positive predictive value, and negative predictive value of 86%, 58%, 54%, and 88%, respectively, and values of 90%, 57%, 60%, and 89%, respectively, at diagnosis. The median proportion of CD45−/CD56+ cells in MFC was 0.028% (range 0–35%). The event-free survival (EFS) rates for MFC (+) and MFC (−) patients according to the analysis results of the BM samples at the time of diagnosis were 70.6% and 81.8%, respectively (p = 0.607), and the overall survival (OS) rates were 88.2% in MFC (+) patients and 90.9% in MFC (−) patients (p = 0.583). Conclusion: Multicolor flow cytometry may be used as an adjunct to cytomorphology to achieve more sensitive and accurate results as an objective, quantitative method with fast results in detecting bone marrow involvement in children with NB.